Back Cover: Visualizing an Ultra‐Weak Protein–Protein Interaction in Phosphorylation Signaling (Angew. Chem. Int. Ed. 43/2014). Issue 43 (14th August 2014) - Xing, Qiong; Huang, Peng; Yang, Ju; Sun, Jian‐Qiang; Gong, Zhou; Dong, Xu; Guo, Da‐Chuan; Chen, Shao‐Min; Yang, Yu‐Hong; Wang, Yan; Yang, Ming‐Hui; Yi, Ming; et al.
<x xml:space="preserve">Abstract</x> Proteins interact …︁ in a transient yet specific manner to relay signals within the crowded cellular environment. In their Communication on page 11501 ff., C. Tang, W.‐P. Zhang, and co‐workers show that phosphorylation signaling can take place between two proteins with a binding affinity of only 25 mM and a complex lifetime in the μs–ms range, which is an order of magnitude weaker than all known protein–protein interactions. Such ultra‐weak and fleeting interactions could be prevalent among signaling proteins.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>